The Significance of Intellectual in Improving the Existence of the Religious Communities Ibn Sina Perspective - Khair, Nurul (Proceeding International Conference on Science and Engineering, 2019)
This paper is a review of Ibn Sina's literature on the significance of reason in increasing religious knowledge. Ibn Sina shared knowledge, hudhuri and husuli. The knowledge of hudhuri is necessary or self-knowledge, so that the truth cannot be doubted. Conversely, knowledge of husuli is non-necessary knowledge which requires argumentation by building prescriptions to justify the information obtained in reality. Ibn Sina studied husuli as a serious discussant in his epistemology study. Perception of the reason is the main basis for justifying information obtained through objects of knowledge, especially religion. Religion contains mystical values that cannot be easily understood through sensory persepsies. Reason is a justification that guides humans to find conclusions that can be objectively justified. However, it is known that the phenomenon of religious communities, especially millennial communities - understanding religious values is not based on reason, but rather perceptual power that implies the existence of shahwati and ghodobiyah encouragement, resulting in a radical paradigm in the existence of religious communities. The purpose of this paper is to know the significance of reason for human life and to respond to the fallacy in understanding religious values. The results of this study are knowing the significance of reason in increasing the knowledge and existence of religious communities to understand religious values. The implication is that it forms an anti-radical paradigm and is objective towards religious values.